Chitosan-alginate nanoparticles of cabazitaxel: Design, dual-receptor targeting and efficacy in lung cancer model - Vikas; Mehata A.K.; Suseela M.N.L.; Behera C.; Kumari P.; Mahto S.K.; Muthu M.S. (My University, 2025)
Cabazitaxel (CZT) loaded chitosan-alginate based (CSA) nanoparticles were developed with dual targeting functions of both folate receptor and epidermal growth factor receptor (EGFR) using ionic gelation technique. The chitosan-folate conjugate was synthesized, and characterized by using FTIR, NMR and Mass spectroscopy. The physicochemical parameters and morphology of all CSA nanoparticles were examined. The degree of conjugation of folic acid and cetuximab (CTXmab) was determined by UV–Visible spectroscopy and Bradford assay, respectively. Moreover, XPS analysis also supported the presence of the ligands on nanoparticles. The cellular-uptake study performed on A-549 cells demonstrated a significant enhancement in the uptake of dual-receptor targeted CSA nanoparticles than non-targeted and single-receptor targeted CSA nanoparticles. Further, CZT-loaded dual receptors targeted CSA nanoparticles also showed significantly lower IC50 values (~38 folds) than the CZT control against A-549 cells. Further, in-vivo histopathological evaluations of dual receptor-targeted CSA nanoparticles have demonstrated better safety in Wistar rats. Moreover, its treatment on the Benzo(a)pyrene (B(a)P) induced lung cancer mice model has showed the enhanced anticancer efficacy of CZT with a prolonged survival rate. © 2022 Elsevier B.V.